INVERTEBRATE ANIMALS OF ETHNOMEDICOZOOLOGICAL IMPORTANCE IN MANIPUR - SINGH, K. KHAMBA; SINGH, R.K. GAMBHIR; ANAND, LAITONJAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
The present paper highlights the ethnomedicozoological aspects of 22 invertebrate animals belonging to different phyla of animal kingdom, as practised by the Meetei community of Manipur, India.